Emotional development recent research advances - Nadel, Jacqueline; Muir, Darwin (Oxford University Press, 2005)
From prenatal life upwards, our emotions play a central role in our development. Exactly how emotions shape our lives is less clear. This book includes views from neuroscience, primatology robotics, psychopathology, and prenatal development. It also includes studies of emotional development in both normal and clinical populations.